Labor Utilization Inefficiency: A Literature Review of Studies on Underemployment and Skills Mismatch in Indonesia - Arif Zulkarnain; Nur Haminati; Misdawita Misdawita; Sufnirayanti (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2025)
This study analyzes the issue of labor utilization in Indonesia, which is still far from efficient. The main focus is on the phenomena of underemployment and skills mismatch as the fundamental issue of labor market inefficiency. Interestingly, although open unemployment statistics show very low figures, the productive capacity of most of our workforce has not been fully drawn into the labor market. This is reflected in the minimal working hours, low productivity, and the gap between educational qualifications and professional requirements. Through a literature review that synthesizes national data and international reports, this study finds that underemployment in Indonesia is based on structural problems, such as the strong influence of the informal sector and economic inequality between regions. Moreover, the phenomenon of over-education is a clear manifestation of human capital wastage. In summary, the efficiency of the Indonesian labor market cannot be assessed solely on the basis of formal unemployment figures; closer synchronization between the education system and industry needs is required.